Is judgment reactivity really about the judgment? - Myers, Sarah J., author; Rhodes, Matthew, advisor; Cleary, Anne, committee member; Fisher, Gwen, committee member; Folkestad, James, committee member (Colorado State University. Libraries, 2023)
A common research tool used to measure one's understanding of their own learning is to collect judgments of learning (JOLs), whereby participants indicate how likely they are to remember information on a later test. Importantly, recent work has demonstrated that soliciting JOLs can impact true learning and memory, referred to as JOL reactivity. However, the underlying cognitive processes that are impacted when learners make JOLs and that lead to later reactivity effects are not yet well-understood. To better elucidate the mechanisms that drive JOL reactivity, I examined how changing the method of soliciting JOLs impacts reactivity. In Experiment 1, I manipulated how long participants had to make their JOLs; in Experiment 2, I compared JOLs made on a percentage scale versus a binary (yes/no) scale; and in Experiment 3 participants were required to explain why they made some of their JOLs. Judgments that require or allow for more in-depth processing (i.e., longer time in Experiment 1, percentage scales in Experiment 2, explaining in Experiment 3) should require more effort from participants to make their judgments. If these more effortful judgments lead to larger reactivity effects, it would suggest that reactivity is driven by processes that occur when making JOLs. However, findings from the experiments did not support this account. Although some differences in reactivity effects were seen after making binary and explaining JOLs compared to percentage JOLs, the hypothesis that more cognitive effort would result in stronger reactivity was not supported. Therefore, results suggest that the mere presence of JOLs during study may cause a general shift in participants' learning approach, resulting in later JOL reactivity.
Keywords: metacognition; JOL reactivity